Reconfiguring Teaching in Higher Education: Pedagogical Approaches, Digital Integration, and Faculty Development Needs - Dias, C. C.; Nascimento, G. (XXVII International Symposium of Education on Computers in Education, 2025)
Over the past two decades, higher education in Portugal has undergone a process of structural, organisational, and pedagogical transformation. This study explores faculty development needs and teaching approaches in higher education, within the scope of the project INOV3P, a national initiative promoting pedagogical innovation in nontechnological higher education fields in Portugal. The study applies the HEAT and TPACK frameworks, to 105 faculty members at Iscte in tandem to identify four distinct teaching profiles based on pedagogical approaches and self-efficacy. By cross-referencing these with training needs, the findings provide actionable insights for designing targeted, profile-sensitive faculty development policies aimed at promoting studentcentred and digitally integrated teaching.